Improving uniformity and reliability of SRAM PUFs utilizing device aging phenomenon for unique identifier generation. (August 2019) - Garg, Achiranshu; Lee, Zhao Chuan; Lu, Lu; Kim, Tony Tae-Hyoung
Abstract: SRAM Physical Unclonable Functions (PUFs) utilize start-up values generated by random variations in the fabrication process. However, the random variations can generate biased power-up data, which can degrade the uniformity below the target. In addition, very small mismatches can prevent power-up data from being repeated, deteriorating the reliability. This paper presents a post-fabrication technique that can improve the uniformity and the reliability of SRAM PUFs by utilizing device aging phenomenon through two functional steps. In the first step, the proposed technique controls the polarity of the device aging in each SRAM cell using the power-up value for uniformity improvement. Once a target uniformity is achieved from an SRAM array, we inject device aging into each SRAM cell in a way of increasing the mismatches between two cross-coupled inverters. An SRAM PUF test chip fabricated in 65 nm CMOS technology validated the effectiveness of device aging in enhancing the uniformity and the reliability of the SRAM PUF.